+0  
 
0
138
1
avatar

Simplify the following expression. Write the answer without negative exponents and use only fractions if necessary (no decimals).

12^a−1b^10/−3a^−9b^−4

 Oct 24, 2018
 #1
avatar+21848 
+9

Simplify the following expression.
Write the answer without negative exponents and use only fractions if necessary (no decimals).

 

\(\begin{array}{|rcll|} \hline && \dfrac{12^{a-1}b^{10}}{-3a^{-9}b^{-4}} \\\\ &=& - \dfrac{12^{a-1}b^{10}}{3a^{-9}b^{-4}} \\\\ &=& - \dfrac{12^{a}12^{-1}b^{10}}{3a^{-9}b^{-4}} \\\\ &=& - \dfrac{12^{a}b^{10}}{3\cdot 12^1a^{-9}b^{-4}} \\\\ &=& - \dfrac{12^{a}b^{10}}{36a^{-9}b^{-4}} \\\\ &=& - \dfrac{12^{a}b^{10}a^{9}b^{4}}{36} \\\\ &=& - \dfrac{12^{a}a^{9}b^{10}b^{4}}{36} \\\\ &=& - \dfrac{12^{a}a^{9}b^{10+4}}{36} \\\\ &=& - \dfrac{12^{a}a^{9}b^{14}}{36} \\ \hline \end{array} \)

 

laugh

 Oct 24, 2018

15 Online Users

avatar
avatar
avatar
avatar
avatar
avatar